QTL mapping for wheat ferulic acid concentration using 50 K SNP chip in a recombinant inbred line population of Zhongmai 578/Jimai 22 - Rabiu Sani Shawai; Wenfei Tian; Siyang Liu; Xue Gong; Jindong Liu; Shuanghe Cao; Yong Zhang; He Zhonghu (Wiley, 2024)
Background and Objectives: Ferulic acid is a prominent bioactive compound found in wheat grains, known for its beneficial health effects, prompting significant interest from breeders and producers. The aim of this study was to identify new quantitative trait loci (QTL) to aid in the development of wheat varieties with increased ferulic acid concentration (FAC). Findings: In this study, a recombinant inbred line population, resulting from a cross between Zhongmai 578 and Jimai 22, was evaluated in five different environments. Genotyping was performed using the wheat 50K single‐nucleotide polymorphism (SNP) array. Three stable QTL, named QFAC.caas‐2D, QFAC.caas3B, andQFAC.caas‐4D, were identified. These QTL explained 4.24%–7.09%, 3.7%–4.57%, and 3.20%–5.06% of the phenotypic variances, respectively. Furthermore, three SNPs closely associated with above QTL were successfully converted into kompetitive allele‐specific polymerase chain reaction (KASP) markers. Conclusions: FAC is a complex trait governed by multiple minor‐effect QTL. The successful development of KASP markers opens up avenues for markerassisted selection in breeding programs. Significance and Novelty: This study establishes a genetic foundation for understanding the genetic basis of FAC in wheat. The identified QTL and developed KASP markers offer valuable insights for quality breeding initiatives and the production of functional wheat‐based foods.